IN-VITRO CAPACITATION OF BOVINE SPERMATOZOA BY MEASURING PENETRATING POTENTIAL - SINGH, S; GUPTA, H P; MISHRA, A K; KUMAR, A (The Indian Journal of Animal Reproduction, 2023)
Penetrating potential of bovine spermatozoa, capacitated in vitro, w~ studied in terms of sperm penetratiodistance (SPD) to determine the suitable combination of caffeine concentration and incubation period foroptimu~capacitation. The capacitation was induced in sperm TALP (Tyrode'S albumin, lactate and pyruvate) mediumcontaining 0, 5, 10 and 20 mM caffeine at 39 °C for 0, 30, 60 and 90 min. The c~pacitated spermatozoa weresubjected to penetration in 2% polyacrylamide gel and SPD was measured. The maximum SPD of 19.35±0.50mm /hr was recorded at 20mM caffeine with 90 min incubation period indicating this period and concentrationcombination as the most effective enhancer of in vitro capacitation of bovine spermatozoa.
Keywords: Buffalo spermatozoa; Caffeine; Capacitation; Gel penetration